Development of a carbohydrate‐supplemented semidefined medium for the semiselective cultivation of Lactobacillus spp. (12th June 2013) - Menon, R.; Shields, M.; Duong, T.; Sturino, J.M.
Abstract : Abstract: The macronutrient and micronutrient compositions of traditional media used to cultivate Lactic Acid Bacteria (LAB) are largely undefined, which precludes their use in many metabolic bioassays. In order to address this deficiency, we developed MS: a carbohydrate‐supplemented semidefined medium with low‐background coloration. MS was designed to support the semiselective cultivation of a wide range of fastidious species belonging to the Lactobacillus clade of the LAB. When supplemented with 100 mM D‐glucose, the MS medium stimulated the proliferation of 21 strains of LAB, including Pediococcus spp. and Lactobacillus spp. The MS medium supported biomass accumulation comparable with MRS, an undefined medium routinely used for the cultivation of lactobacilli. Interestingly, however, the novel MS medium exhibited greater semiselectivity against non‐LAB than MRS. Together, these results suggest that MS is an acceptable alternative to MRS for use in metabolic and phenotypic bioassays that use a colorimetric reporter system or would benefit from a semidefined nutrient composition. Significance and Impact of the Study: The objective of this study was to develop a MRS‐like semidefined medium with improved background coloration and the carbon‐source supplemental properties of M17 broth to support the semiselective proliferation of fastidious lactobacilli. The resultant medium, MS, supported biomass accumulation at levels comparable with MRS; however, the new MS medium exhibited greater semiselectivity against non‐Lactic Acid Bacteria than MRS. Together, these results suggest that MS is an acceptable alternative to MRS for use in metabolic and phenotypic bioassays, especially for those that use a colorimetric reporter system or would benefit from a semidefined nutrient composition. Abstract : Significance and Impact of the Study: The objective of this study was to develop a MRS‐like semidefined medium with improved background coloration and the carbon‐source supplemental properties of M17 broth to support the semiselective proliferation of fastidious lactobacilli. The resultant medium, MS, supported biomass accumulation at levels comparable with MRS; however, the new MS medium exhibited greater semiselectivity against non‐Lactic Acid Bacteria than MRS. Together, these results suggest that MS is an acceptable alternative to MRS for use in metabolic and phenotypic bioassays, especially for those that use a colorimetric reporter system or would benefit from a semidefined nutrient composition.